Karakteristik Morfologi Tanaman Sukun (Artocarpus alltilis Forst) Di Kabupaten Seram Bagian Barat - Penohaq, L O; Jambormias, Edizon; Kesaulya, Henry (Fakultas Pertanian, Universitas Pattimura, 2023)
Morphological characteristics are inherent properties of plants and are indicated by plant structural components and are related to organs that can be observed and can be characterized. This study aims to characterize the morphology of breadfruit plants in the West Seram District. The morphological characters observed included tree shapes, leaves, flowers, and fruit. Morphological characterization refers to Key Characterization and Evaluation Descriptors: Methodologies for the Assessment of 22 Crops. Dendogram formed based on hierarchical cluster analysis. Plant height reaches ± 37m, with a stem diameter of 193cm, leaf length of 75cm, width of 45cm, petiole length of 9 cm, the longest male flower length is 13cm and flower diameter is 70cm, the longest fruit length is 28cm, and the fruit weight is 1,310 kg, stalk longest flower 9 cm. There is a diversity of morphology with different similarity indices.